RESTRICTION ON THE RIGHTS OF PARTICIPANTS IN PRE-TRIAL PROCEEDINGS IN CRIMINAL PROCEDURE - KACHALOV Egor Viktorovich (Правовое государство: теория и практика, 2022)
The purpose of the article is to study the legal essence of restricting the rights of participants in pre-trial proceedings in criminal procedure, the specific goals of their restriction, the list of rights that may be subject to restriction, grounds, criteria, conditions, as well as limits of restriction. The article uses methods of system analysis, synthesis and generalization. Results: the author concludes that the system of restricting the rights of participants in pre-trial proceedings in criminal cases includes: objectives, grounds, conditions, criteria and limits of restriction; the powers of officials provided for by the criminal procedure law to restrict the rights of participants in proceedings; procedural rights of participants in criminal proceedings, the exercise of which is aimed at ensuring that coercive measures are not applied to them; procedure and terms for restricting the rights of participants in pre-trial proceedings, which vary depending on which right is subject to restriction; control over the restriction on the rights of participants in pre-trial proceedings (procedural control, prosecutorial supervision, judicial control). The specific purpose of restricting rights in pre-trial proceedings is to ensure the proper conduct of criminal proceedings. The limits of restriction on the rights of participants in pre-trial proceedings are determined by the specific purpose of legal restriction, the nature and specificity of the investigative or procedural action, in the exercise of which the rights are restricted by the discretion of the official, who decides on the specific restriction, which is formed on the assessment of the actual situation, the characteristics of the person whose rights are subject to restriction. Any restrictions on rights are exercised only on the basis of a procedural decision by an official (inquirer, investigator, court) in accordance with the law and if there are grounds for it. The most significant restrictions on the rights of participants in criminal proceedings are permitted only by a judicial decision.